الجريدة الرسمية _ العدد 29 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 1898 لسنة 2024 -- قرار رقم 1899 لسنة 2024 -- قرار رقم 1981 لسنة 2024 -- قرار رقم 1982 لسنة 2024 -- قرار رقم 1983 لسنة 2024 -- قرار رقم 1984 لسنة 2024 -- قرار رقم 1985 لسنة 2024 -- قرار رقم 1986 لسنة 2024 -- قرار رقم 1987 لسنة 2024 -- قرار رقم 1988 لسنة 2024 -- قرار رقم 1989 لسنة 2024 -- قرار رقم 1990 لسنة 2024 -- قرار رقم 2208 لسنة 2024 -- قرار رقم 2209 لسنة 2024 -- قرار رقم 2210 لسنة 2024 -- قرار رقم 2211 لسنة 2024